SECTARIAN CONFLICT IN ELITE NEWSPAPERS OF PAKISTAN: A PEACE JOURNALISM PERSPECTIVE - Dr. Usman Quddus (Journal of Peace, Development and Communication, 2021)
Mass Media occupies a significant place in contemporary era of volatile changes and in a country like Pakistan, which is hovered by internal and external conflicts since its inception, it turns pivotal. The geo-strategic depth and ethno-political structure of the country has highlighted the sensitivity of media reporting and its implications on a wider scale. The ingrained private media outlets in 2000 have grown mature over the past 20 years. Yet the reporting dilemmas haunt the underdeveloped nation. The present study aims to explore the emerging sectarian unrest in the country and its coverage in elite English newspapers Dawn and The News over the years 22019, 2021 using census technique to examine the existence and frequency of war and peace frames by John Galtung, and thus finds the role of media escalatory in nature. Keywords: Mass Media occupies a significant place in contemporary era of volatile changes and in a country like Pakistan, which is hovered by internal and external conflicts since its inception, it turns pivotal. The geo-strategic depth and ethno-political structure of the country has highlighted the sensitivity of media reporting and its implications on a wider scale. The ingrained private media outlets in 2000 have grown mature over the past 20 years. Yet the reporting dilemmas haunt the underdeveloped nation. The present study aims to explore the emerging sectarian unrest in the country and its coverage in elite English newspapers Dawn and The News over the years 22019, 2021 using census technique to examine the existence and frequency of war and peace frames by John Galtung, and thus finds the role of media escalatory in nature. Keywords: Sectarian Conflict, War Journalism, Peace Journalism, escalatory , War Journalism, Peace Journalism, escalatory